Vulnerability Assessment of Urban Rail Transit Network—A Case Study of Chongqing - Lan Xu; Pengcheng Xiang; Yan Qian; Simai Yang; Tao Zhou; Feng Wang (Buildings, 2025)
Urban rail network vulnerability assessment has become the core of the urban public transport system. Identifying and quantifying the vulnerability of urban rail transit is the key to coping with the crisis situation of the urban rail transit system. The article uses the Space L method based on complex network theory to establish a topological model of the Chongqing rail transit line network, analyze the topological properties of the network, and use MATLAB 2020b software to conduct deliberate attacks on each station to assess the vulnerability of the Chongqing rail transit network in terms of changes in network efficiency. The results show that the density of Chongqing’s rail transit network is low and the network level needs to be improved; there is no significant correlation between the node vulnerability and the degree value of nodes in the network. The identification of important stations can provide a basis for the decision-making of urban rail transit operation managers and has a strong practical value.